Diseño de un programa de capacitación sobre la violencia intrafamiliar dirigido a los padres de familia de los 8º años de EE.BB para mejorar el rendimiento académico en el colegio técnico "Pujilí" en el año lectivo 2012 - 2013 - Mallitasig Velasco, José Luis (2015)
The present investigation was based on the design of a training program on domestic violence aimed to the parents Pujilí Technical College, to improve the academic performance of students in the 8th year of EGB specifically he helped strengthen the relations between parents and children demonstrating the causes and consequences associated with the violence. Since causes a lot of pain in homes as family as: dysfunction, low self-esteem of family ties, becoming in turn a coexistence of aggression to the emotional development of students. This is expressed from small attitudes, jokes, insults, beatings, punishment; which they are frequent in the victims, and certainly can be avoided….